Improvement of the Patient Safety Culture in the Primary Health Care Corporation – Qatar. Issue 8 (17th December 2021) - El Zoghbi, Mohamad; Farooq, Saad; Abulaban, Ali; Taha, Heba; Ajanaz, Sajna; Aljasmi, Jawaher; Ahmad, Shakil; Said, Hana
Abstract : Objectives: Primary Health Care Corporation (PHCC) is the public primary health care provider in Qatar. Having a patient safety culture (PSC) is the keystone to enabling a continuous process to improve the quality of services and to reduce errors. The objective of this study was to assess the impact of accreditation, quality improvement trainings, and patient safety (PS) trainings on the improvement of the PSC at the PHCC in Qatar. Methods: The Medical Office Survey on Patient Safety Culture from the Agency for Healthcare Research and Quality was used in 2012 and 2015 to assess the culture of PS and health care quality in the 21 health centers. The results of the two surveys were compared using the χ 2 test. A P value of less than 0.05 was considered significant. Results: Out of 2689 staff working in the 21 health centers, 1810 (67.3%) completed the survey in 2012, and 2616 (70.0%) of 3735 completed the survey in 2015. The comparison between 2012 and 2015 survey's results showed a statistically significant improvement for all the 10 dimensions ( P < 0.05). Although a statistically significant difference was observed between 2012 and 2015 results for work pressure and pace, three of the four questions of the work pressure and pace dimension presented nonsignificant differences. Conclusions: The survey was a good tool to raise awareness on PS and quality issues at PHCC. There is evidence that the implementation of accreditation program, the quality improvement trainings, and PS trainings helped the organization improve its PS culture.